2019
DOI: 10.1371/journal.pone.0216164
|View full text |Cite
|
Sign up to set email alerts
|

A bidimensional measure of empathy: Empathic Experience Scale

Abstract: Empathy is a key notion in the study of sociality. A phenomenological perspective on empathy as intersubjective understanding offers a common ground for multiple dimensions. Corresponding to the dichotomy between perceptual and cognitive levels, two constructs can be distinguished: vicariously experiencing and intuitively understanding others’ emotions. We developed and validated a new questionnaire for the assessment of individual differences in empathy. In a first study (N = 921), we created a questionnaire … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
20
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(55 citation statements)
references
References 94 publications
6
20
0
2
Order By: Relevance
“…Our exploratory factor analysis, consideration of the distinct cognitive and affective domains of empathy, and dyadic CFA suggested that a refined, shortened IRI scale is an acceptable measure of empathy in this population of adult partners living with HIV in Zambézia Province, Mozambique. Instead of the original four factor structure, exploratory factor analyses suggested, and the CFA with dyadic invariance testing confirmed, two empathy subscales: an affective subscale (with items assessing personal distress and empathetic concern) and a cognitive scale (with items assessing perspective taking and fantasy), which aligns with more recently developed empathy scales and recent data that describe the neurological processes underlying empathy [25][26][27][28][29]. The obtained subscales were moderately correlated with each other and had comparable intra-scale reliabilities among women and men.…”
Section: Discussionsupporting
confidence: 61%
See 3 more Smart Citations
“…Our exploratory factor analysis, consideration of the distinct cognitive and affective domains of empathy, and dyadic CFA suggested that a refined, shortened IRI scale is an acceptable measure of empathy in this population of adult partners living with HIV in Zambézia Province, Mozambique. Instead of the original four factor structure, exploratory factor analyses suggested, and the CFA with dyadic invariance testing confirmed, two empathy subscales: an affective subscale (with items assessing personal distress and empathetic concern) and a cognitive scale (with items assessing perspective taking and fantasy), which aligns with more recently developed empathy scales and recent data that describe the neurological processes underlying empathy [25][26][27][28][29]. The obtained subscales were moderately correlated with each other and had comparable intra-scale reliabilities among women and men.…”
Section: Discussionsupporting
confidence: 61%
“…In the absence of a theoretical framework to explain mixing of cognitive and affective items, we selected the two-factor solution (distinct cognitive and affective empathy factors) to minimize these discrepancies. This aligns with more recently developed empathy scales and the number of factors on the IRI for couples scale, which allows for improved interpretability of the two-factor solution instead of the three-or four-factor solutions, which had subscale mixing that limited interpretability [25,28]. Across ten imputed datasets, factor correlations ranged from 0.56 to 0.59.…”
Section: Exploratory Factor Analysissupporting
confidence: 67%
See 2 more Smart Citations
“…De acuerdo con Duan y Hill (1996), la empatía puede ser vista desde tres perspectivas teóricas: (a) un rasgo de la personalidad o habilidad, (b) una secuencia de experiencias y (c) una situación específica de estados cognitivos-afectivos, que es la más influyente (Blair, 2005;Innamorati, Ebisch, Gallese y Saggino, 2019;Sugarman, Nemirrof y Greenson, 2001;Vaish, Carpenter y Tomasello, 2009), dado que existen diversos estudios en los que la estruc-tura cognitivo-afectiva forma parte de algunos test (Vachon et al, 2014). Así, lo afectivo involucra respuestas emocionales respecto a la situación con un otro (Cohen y Strayer, 1996;Decety, 2011;Eisenberg y Fabes, 1990;Eisenberg, Fabes y Spinrad, 2006;Zaki, 2014) y lo cognitivo hace referencia a la comprensión emocional de otra persona, a través de asociaciones simples (Cox et al, 2011;Hoffman, 1977;Schnell, Bluschke, Konradt y Walter, 2011).…”
Section: Introductionunclassified